Phytochemical Profile and Antioxidant Potential of Zingiberaceae and Solanaceae Plants Using the RAMES Method - Adilah, Hanifa Nur; Adawiyah, Suryani; Agustiana, Syifa; Effendi, Alvira Noer; Sinaga, Ernawati (Universitas Nasional Jakarta, 2025)
Plants from the Zingiberaceae and Solanaceae families are recognized for their diverse phytochemical content and pharmacological potential. This study aimed to evaluate the phytochemical profiles and antioxidant activities of ten plant species from these families using the Rapid Metabolome Extraction and Storage (RAMES) method. Fresh rhizomes from Zingiberaceae and fruits from Solanaceae were extracted with ethanol, followed by qualitative phytochemical screening and antioxidant evaluation using the ABTS method. All tested species contained alkaloids, flavonoids, tannins, quinones, and phenols. Triterpenoids were consistently detected in Zingiberaceae species but were largely absent in Solanaceae, which predominantly contained steroids. Antioxidant assays revealed strong activity in all samples, with complete ABTS decolorization (score +3) comparable to ascorbic acid. These findings suggest that antioxidant potential is closely associated with flavonoid and phenolic compound content. The RAMES method proved to be a rapid, efficient, and environmentally friendly approach for small scale extraction of bioactive compounds, enabling sustainable use of medicinal plant resources. This study underscores the therapeutic potential of Zingiberaceae and Solanaceae species as natural antioxidant sources for the development of functional health products and herbal medicines. Further quantitative and biological studies are recommended to identify key active constituents and evaluate their safety and clinical efficacy.